PENDAMPINGAN IBU MENYUSUI PADA MASA PANDEMI COVID 19 UNTUK MENINGKATKAN PEMBERIAN LAKTASI - ZULAIKHA, LAYLA IMROATU; ELIYANA, YAYUK; SURYANINGSIH, SURYANINGSIH (NHM PRESS, 2021)
he existence of the COVID 19 pandemic that attacked all levels of society without exception caused some 239 hospitals (17.9%) to experience a decrease in access to direct lactation supervision, because 72.9% of maternity patients were sent home less than 48 hours after delivery which aims to minimize the transmission of COVID -19 in mothers and newborns. This condition increases the concern that breastfeeding mothers can transmit COVID-19 during the lactation process. For this reason, it is necessary to have a mentoring process on lactation management. This research is a quantitative research with a one group pre test post test design approach. Then in the data analysis using the Wilcoxon signed rank test statistical test. With the mentoring process about lactation, it can affect the mother's understanding of the benefits and the correct way of breastfeeding so as to improve the mother's behavior in giving lactation.